Vitamin B12 deficiency: Characterization of psychometrics and MRI morphometrics. (February 2016) - Hsu, Yen-Hsuan; Huang, Ching-Feng; Lo, Chung-Ping; Wang, Tzu-Lan; Tu, Min-Chien
Abstract : Objectives: Vitamin B12 is essential for the integrity of the central nervous system. However, performances in different cognitive domains relevant to vitamin B12 deficiency remain to be detailed. To date, there have been limited studies that examined the relationships between cognitions and structural neuroimaging in a single cohort of low-vitamin B12 status. The present study aimed to depict psychometrics and magnetic resonance imaging (MRI) morphometrics among patients with vitamin B12 deficiency, and to examine their inter-relations. Methods: We compared 34 consecutive patients with vitamin B12 deficiency (serum level ≤250 pg/ml) to 34 demographically matched controls by their cognitive performances and morphometric indices of brain MRI. The correlations between psychometrics and morphometrics were analyzed. Results: The vitamin B12 deficiency group had lower scores than the controls on total scores of Mini-Mental Status Examination (MMSE) and Cognitive Abilities Screening Instrument (CASI) (both P < 0.05), language ( P < 0.01), orientation ( P < 0.01), and mental manipulation ( P < 0.05). The patients also showed a greater frontal horn ratio than the controls ( P < 0.05). Bicaudate ratio, fronto-occipital ratio, uncotemporal index, and normalized interuncal distance all showed a strong correlation with the total score of MMSE and CASI (all P < 0.01). Among these psychometric and morphometric indices, pronounced correlations between bicaudate ratio and long-term memory, mental manipulation, orientation, language, and verbal fluency were noted (all P < 0.01). Discussion: Vitamin B12 deficiency is associated with a global cognition decline with language, orientation, and mental manipulation selectively impaired. Preferential atrophy in frontal regions is the main neuroimaging feature. Although the frontal ratio highlights the relevant atrophy among patients, the bicaudate ratio might be the best index on the basis of its strong association with global cognition and related cognitive domains, implying dysfunction of fronto-subcortical circuits as the fundamental pathogenesis related to vitamin B12 deficiency.